The economics of modernization - Goh, Keng Swee, 1918-2010 (Marshall Cavendish Academic, 2004)
Modernization is a vital strategy against centuries of poverty. For success to be achieved, the ethos of traditional society and the old order must give to new beliefs and values (which stress efficiency, law and order, merit through achievement), and a strong effective government able to put through difficult, unpopular, but necessary measures. This is the unifying thread of the collection of Dr Goh's speeches in this volume. (30 speeches and essays, 1961-71).